CONTROL OF HINDMARSH-ROSE MODEL BY NONLINEAR-OPEN-PLUS-CLOSED-LOOP (NOPCL) - Tounsia Benzekri (European Scientific Journal, ESJ, 2014)
In this work, we use the Nonlinear-Open-Plus-Closed-Loop (NOPCL) method to control a nonlinear model: the Hindmarsh-Rose model in which we can exhibit regular and chaotic dynamics. The aim of the NOPCL method is to entrain complex dynamics to arbitrary given goal dynamics, by adding a suitable control term to the system. We use this method to suppress chaos, by entraining chaotic dynamics to a periodic one for the Hindmarsh-Rose model.